A Contemporary Approach to Entrepreneurship Education and Training - Rusok, Nur Hazelen Mat; Kumar, Naresh; Ab Rahman, Siti Maziah (International Journal of Asian Social Science, 2017)
The higher learning institutions (HEIs) should constantly strives to strengthen and enhance efforts to promote the inculcation of entrepreneurship values among the students. Indeed the HEIs should be a catalyst for long-term development of an entrepreneurial culture and assist in providing a conducive entrepreneurship ecosystem. Besides, HEIs encouraged to act as a bridge between academics, industry, entrepreneurs and relevant agencies and be able to coordinate the development of entrepreneurship education aligned with national policies. HEIs entrusted to look at entrepreneurship in a holistic manner so they can contribute to the desired human capital development as well as nation building. In this vein, innovative entrepreneurship education model is timely and that requires a strong research initiative. In this article we have proposed innovative entrepreneurship education model and measurement tool that fits different types of institutional settings. The entrepreneurship framework highlights the practice and reliable ways of assessing the innovative entrepreneurship building success.